If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2(3x-10)+8x=7+20+7x
We move all terms to the left:
-2(3x-10)+8x-(7+20+7x)=0
We add all the numbers together, and all the variables
-2(3x-10)+8x-(7x+27)=0
We add all the numbers together, and all the variables
8x-2(3x-10)-(7x+27)=0
We multiply parentheses
8x-6x-(7x+27)+20=0
We get rid of parentheses
8x-6x-7x-27+20=0
We add all the numbers together, and all the variables
-5x-7=0
We move all terms containing x to the left, all other terms to the right
-5x=7
x=7/-5
x=-1+2/5
| 3/5x+2/3+x=1/2–1/5x | | −2/3x+11=-1 | | a-3÷5=3 | | a-3÷5=4 | | 2z-9=-z-3 | | 3/10+4/5x=1/2 | | −23x+11=-1 | | 42=x+(2x+2) | | 1.0=4.0+y | | 5r-8=38 | | -90=-6c | | 5n+49=55 | | 62=x+(3x-6) | | g+-63=13 | | z-9=2z | | -4x-2(7x+1)=-(-2x-8) | | -3(4-7x)=38 | | 4=-1/7x | | X+5x-13=143 | | 7h-16=0 | | 2/5Xx=3/20 | | 3+2x=3x-55 | | 6+1.2x=12 | | -42+p=-52 | | 26=10x+16x | | 2/5Xz=3/20 | | 12x+8-10=4 | | 5(x-10)=3x-20 | | -6x+4+x=-1 | | 30-6x=10-26x | | 3x+1+4x-7=90 | | 5/3(m-2)=7 |